2016
DOI: 10.1111/bjd.14459
|View full text |Cite
|
Sign up to set email alerts
|

IgE and Fcε RI are highly expressed on innate cells in psoriasis

Abstract: IgE might participate in the development of psoriasis by activating FcεRI-bearing cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 36 publications
2
22
1
Order By: Relevance
“…The result is consistent with some studies [7][8][9][10][11]. Yan et al demonstrated that 39% of patients with psoriasis had elevated serum IgE concentrations and they observed that lesional skin of patients with psoriasis contains more IgE+ and FceRI+ cells [20]. Chen et al reported that the serum IgE level was elevated in 46% psoriatic patients [11].…”
Section: Discussionsupporting
confidence: 90%
“…The result is consistent with some studies [7][8][9][10][11]. Yan et al demonstrated that 39% of patients with psoriasis had elevated serum IgE concentrations and they observed that lesional skin of patients with psoriasis contains more IgE+ and FceRI+ cells [20]. Chen et al reported that the serum IgE level was elevated in 46% psoriatic patients [11].…”
Section: Discussionsupporting
confidence: 90%
“…Its efficacy has been shown even for psoriatic patients with high total serum IgE levels and, indeed, UST lowered the number of IgE-and FceRI-bearing cells in the lesional skin. 5 However, previous case reports have also documented that UST provoked or exacerbated AD-like symptoms paradoxically while improving psoriatic symptoms. 6,7 We also experienced a similar reciprocal phenomenon following UST administration in a couple of psoriatic patients.…”
Section: Discussionmentioning
confidence: 97%
“…Ustekinumab is one of the most commonly used biologics in psoriatic patients. Its efficacy has been shown even for psoriatic patients with high total serum IgE levels and, indeed, UST lowered the number of IgE‐ and FcεRI‐bearing cells in the lesional skin . However, previous case reports have also documented that UST provoked or exacerbated AD‐like symptoms paradoxically while improving psoriatic symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MC and its mediators are increased in psoriatic lesional skin . Moreover, increased levels of FcεRI receptor, the high‐affinity surface receptor for IgE implicated in mediating MC allergic responses, have recently been reported in psoriasis. Mast cells are involved in allergy and inflammation and are numerous in the normal skin where they express considerable phenotypic variability, possibly in response to local and systemic neuroendocrine triggers …”
Section: Discussionmentioning
confidence: 99%